Bounce back - Misako Rokkusu 1977- (New York Feiwel & Friends, 2021)
Lilico's life in Japan is going well. She has great friends and is the captain of the school's basketball team. She's happy! Then comes her parents' news: they're moving to America! Before she knows it, Lilico finds herself in Brooklyn, New York, forced to start all over. And that won't be easy with her closest friends thousands of miles away or a school bully who immediately dislikes her. Luckily, anime-loving Nala and Henry eventually befriend Lilico and with help from them--along with her guardian spirit who looks a lot like her cat, Nico--Lilico just might figure out where she fits in.
Ages 8-12